FUNCTION AND ROLE OF ADMINISTRATIVE LAW IN THE PREVENTION AND COMBATING OF CORRUPTION IN INDONESIA - Muhammad Zunan Fanani; M. Zamroni (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
Corruption is defined as an act which was not good as embezzlement, receiving kickbacks and so forth. Corruption has penetrated in every layer of authority, whether in the executive, legislature and judiciary, in both of the layers at the central level to the village level. The quantity and quality is also increasing, along with the improvement of democracy in Indonesia. While the State Administration can be interpreted as directives, government, implementation activities, activity guidance, the creation of the principles of public policy implementation, activity analysis, balancing and presentation decisions, policy considerations, as the work of individuals and groups in producing public goods and services, and as an arena field of academic and theoretical work, in the state government. This study uses the methodology of normative juridical deduction, the judicial approach. At the end of the discussion will be found the answer from the legal issues that the law of the State Administrai important role in the prevention and eradication of corruption. With prescriptions for a legal solution.Â